Case report: Serious unexpected vascular events in two patients with lymphocytic variant hypereosinophilic syndrome - Torcida, Nathan; Casalino, Giulia; Bondue, Antoine; Jodaitis, Lise; Vanden Eynden, Frederic; Roufosse, Florence (Frontiers in Cardiovascular Medicine, 2023)
Background Lymphocytic-variant hypereosinophilic syndrome (L-HES) is a form of reactive hypereosinophilia, most commonly associated with interleukin-5 over-production by clonal, most commonly CD3−CD4+CD2hiCD5hiCD45RO+ T-cells. Patients often present with predominant cutaneous and soft-tissue manifestations, while cardiovascular involvement is uncommon. Methods We reviewed the medical files of two L-HES patients followed in our center who developed serious vascular complications and performed a literature review for similar cases. Results Patient 1, a 52-year-old female, presented with an ischemic stroke secondary to left middle cerebral artery dissection after 10 years of indolent L-HES. Blood eosinophilia was controlled with oral corticosteroids (OCS), but OCS-tapering attempts with hydroxyurea and pegylated interferon failed, prompting the introduction of mepolizumab with rapid normalization. Patient 2, a 62-year-old female, had been asymptomatic for 10 years without treatment when a NSTEMI occurred, due to coronary artery occlusion secondary to a large cauliflower-aneurysm of the proximal aorta and aneurysmal dilatation of several coronary arteries, requiring semi-urgent surgical management. Aortic wall staining for eosinophil major basic protein showed eosinophils in the adventitia. Blood eosinophilia was controlled with OCS. Conclusions Patients with apparently clinically benign L-HES may develop arterial complications, consisting in dissection and/or aneurysm dilatation of medium-to-large vessels with serious consequences. The value of performing regular vascular imaging and monitoring during follow-up has yet to be determined.